Respon Warganet Terhadap Gaya Khitobah Halimah Alaydrus - Pertiwi, Mayang Sri; Ridwan, Aang; Yuningsih, Yuyun (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The aim of this research is to find out how netizens understand and receive Ustadzah Halimah Alaydrus's lecture, and whether there is a desire among netizens to implement the message of Ustadzah Halimah Alaydrus’s lecture. This research uses Hovland's S-O-R theory with qualitative descriptive analysis research methodsThe results of the research showed that 8,50% of comments showed understanding, 77,33% showed acceptance, 14,05% showed a desire to implement the message, and 0,12% showed rejection of his preaching. Based on the good comments of understanding, acceptance and desire, Ustadzah Halimah Alaydrus’s khitobah style can be said to be a contemporary khitobah style that should be emulated and developed by other preachers and preachers.